Chemotherapy and irradiation in childhood Hodgkin's disease. Issue 12 (December 1984) - Robinson, B; Kingston, J; Nogueira Costa, R; Malpas, J S; Barrett, A; McElwain, T J
Abstract : Eighty children aged less than 16 years with newly diagnosed Hodgkin's disease were treated between 1974 and 1982. Complete remission occurred in 95%, with actuarial five year overall survival of 94%, and relapse free survival of 82%: median follow up was 4.8 years. Sixty one children were staged clinically while 19 had staging laparotomies before treatment. Most received combined modality treatment with Ch1VPP chemotherapy (chlorambucil, vinblastine, procarbazine, and prednisolone) followed by irradiation of initial bulk disease. Nodular sclerosis predominated in both sexes, accounting for 60% of the total. Girls with stage IV disease, nodal sclerosis histology, and bulky mediastinal masses had a relatively poor prognosis. Ten children have relapsed, and three prolonged (6 to 7 years) second remissions have been observed. Four died of disease, and one from infection. Clinical staging, avoiding splenectomy, reduced the risk of serious infections. Our current policy is to treat stage IA disease with local irradiation and all other stages with chemotherapy, adding irradiation for bulky mediastinal disease.